Probiotics potential of lactic acid bacteria isolated from Slender Walking Catfish (Clarias nieuhofii) - RAHMAD LINGGA; SUDIRMAN ADIBRATA; OCCA ROANISCA; SIPRIYADI SIPRIYADI; RISKY HADI WIBOWO; AHMAD ARSYADI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lingga R, Adibrata S, Roanisca O, Sipriyadi, Wibowo RH, Arsyadi. 2023. Probiotics potential of lactic acid bacteria isolated from Slender Walking Catfish (Clarias nieuhofii). Biodiversitas 24: 4572-4580. Probiotics are living microorganisms or bioactive agents that positively impact animal digestion. They have successfully isolated from various sources. Recently, we isolated and characterized lactic acid bacteria (LAB) from slender walking fish (Clarias nieuhofii Valenciennes, 1840). The fish sample was obtained from Batu Rusa and Paya Benua Rivers in Bangka Island, Indonesia. LAB was isolated from the fish intestine using the pour plate method. The isolated LAB was then characterized based on their phenotypic traits, biochemical properties, and the 16S rRNA gene identification. The chosen isolates were tested to determine their ability to produce lactic acid, hemolytic and antibacterial activity, and antibiotic resistance. All isolates have the characteristic of rod-shaped and short rod-shaped cells with Gram-positive properties. Isolate KP1 showed the number of populations (2.89 x 107 CFU/mL) and lactic acid production with a concentration of 1.85%. All isolates exhibited no hemolysis activity and displayed sensitivity to antibiotics. The twelve lactic acid bacteria formed clear zones against Staphylococcus aureus and Escherichia coli. The results of the 16S rRNA gene identification indicated that isolates KB4, KB7, KB8, and KP1 belong to Lactobacillus vaginalis, Lactobacillus fermentum, Limosilactobacillus fermentum, and Levilactobacillus brevis, respectively. Lactic acid bacteria isolated from slender walking fish exhibited potential probiotic traits.